Pemanfaatan Limbah Pepaya (Carica papaya L) dan Tomat (Solanum lycopersicum L) Untuk Mempercepat Pengomposan Sampah Organik - Aji Baharudin; Adib Suyanto; Sigid Sudaryanto (Poltekkes Kemenkes Yogyakarta, 2016)
One way to handle organic waste is by utilizing it as raw material for composting. In this study, to accelerate composting time, papaya and tomato waste were used as inoculant. The aim of the study was to know, between the two fruits waste, which one is more effective, by conducting an experiment with post test only group design. As the study object was organic waste from the yard of Dormitory Building I of Yogyakarta Polytechnic of Health, as much as 60 kg and was ob-tained by integrated sampling technique, meanwhile the two fruits waste were 2 kg and obtained from Serangan Market with purposive sampling technique. Based on the indicators of ripe com-post, from five time replications, the average of composting duration in the treatment group of papaya waste inoculant was 32,3 days, while the time in the tomate waste group was 31,7 days. The results of statistical analysis with indepedent t-test at 95 % level of confidence, gained a p-value less than 0,001. It means that the time-difference between two groups of treatment is signi-ficant. To conclude, used tomato waste is more effective and faster than that of papaya in speed-ing-up the composting process.